KUANTIFIKASI KAPAL KARAM BERMATERIAL LOGAM MENGGUNAKAN MULTIBEAM ECHOSOUNDER - Ari Wahyudi; Henry M. Manik; Indra Jaya (Jurnal Teknologi Perikanan dan Kelautan, 2017)
The use of Multibeam echosounder (MBES) equipment for seabed detection has been done by several researchers, which provided intensity values of each research object. However, artificial targets (such as shipwreck) was very dangerous object for ship navigation hence its very important to quantify it. This research was conducted in the Sunda Strait to detect the target of metal shipwreck. The Kongsberg EM 2040 MBES was used along with supporting equipment and SIS software as a data recorder. MBES acquisition results then processed using software CARIS. Display of the results were presented using the software CARIS and Surfer. The results of this study showed that the detection of the shipwreck with MBES Kongsberg EM 2040 is very clear with 3-dimensional shape of the shipwreck. The shipwreck backscattering intensity values have range from -3 to +6.99 dB.